2017
DOI: 10.1002/chem.201700243
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dehydrogenative Coupling of Hydrosilanes with Alcohols for the Production of Hydrogen On‐demand: Application of a Silane/Alcohol Pair as a Liquid Organic Hydrogen Carrier

Abstract: The compound [Ru(p-cym)(Cl) (NHC)] is an effective catalyst for the room-temperature coupling of silanes and alcohols with the concomitant formation of molecular hydrogen. High catalyst activity is observed for a variety of substrates affording quantitative yields in minutes at room temperature and with a catalyst loading as low as 0.1 mol %. The coupling reaction is thermodynamically and, in the presence of a Ru complex, kinetically favourable and allows rapid molecular hydrogen generation on-demand at room t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 74 publications
0
48
0
Order By: Relevance
“…[6][7][8][9][10] to their most known function as a temporary protective group for hydroxyl moieties (e.g., natural products synthesis, derivatization, etc.). [11][12][13][14] There are several methods of their synthesis, starting with classical condensation between alcohols and halosilanes, [15] and finishing on catalytic coupling reactions with hydro-, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] vinyl- [33] or allylsilanes, [34,35] and more recently also with silyl formates. [36][37][38] However, in the case of O-silylation of alcohols with alkynylsilanes -this process has never been comprehensively studied, and previous investigations have mainly referred to the problem of C sp -Si bond stability rather than the application of this transformation as an efficient method for obtaining silyl ethers.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] to their most known function as a temporary protective group for hydroxyl moieties (e.g., natural products synthesis, derivatization, etc.). [11][12][13][14] There are several methods of their synthesis, starting with classical condensation between alcohols and halosilanes, [15] and finishing on catalytic coupling reactions with hydro-, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] vinyl- [33] or allylsilanes, [34,35] and more recently also with silyl formates. [36][37][38] However, in the case of O-silylation of alcohols with alkynylsilanes -this process has never been comprehensively studied, and previous investigations have mainly referred to the problem of C sp -Si bond stability rather than the application of this transformation as an efficient method for obtaining silyl ethers.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, there has been a recent development of non‐covalent support methodologies via π‐interactions, which minimizes the need for chemical modification of the homogeneous catalyst or the support. The group of Peris recently demonstrated that immobilization of N‐heterocyclic carbene Pd II or Ru II complexes onto a graphene surface by noncovalent interactions results in efficient and highly recyclable catalysts for many chemical transformations . We have previously used a polymerizable Pd II NHC complex for the formation of a heterogeneous C–H activation catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…XPS analysis shows that the mild conditions used during the immobilization process preserved the intrinsic properties of both the iridium complex and graphene. 36,46 The coupling of silanes with alcohols is a well-known process for the protection of alcohols and the synthesis of silyl ether derivatives. Transition metal complexes are efficient catalysts for this transformation.…”
Section: Resultsmentioning
confidence: 99%